Australian Marsh Beetles (Coleoptera: Scirtidae). 6. Genera Calvarium Pic, Papuacyphon Zwick, and Ypsiloncyphon Klausnitzer - Zwick, Peter (Zootaxa, 2014)
The genus Calvarium Pic, 1918 is for the first time recorded from Australia. Six new Australian species are named and described. Calvarium australiense n. sp. and C. superbum n. sp. from the Northern Territory are typical representatives of the genus. A new subgenus, Calvariellum n. subgen., is proposed for four species from NE Queensland which share general body structure with other Calvarium species but have different, less derived male genitalia: Calvarium (Calvariellum) bellendenker n. sp., C. (Calvariellum) cochlearifer n. sp., C. (Calvariellum) hamifer n. sp., and C. (Calvariellum) lancifer n. sp.        Papuacyphon darwini n. sp. is described from SW Australia. The genus was previously known only from Papua New Guinea.        Species Group 3 of the genus Ypsiloncyphon Klausnitzer, 2009 is first recorded from Australia. It is endemic to the Australasian region. The Australian species Y. angustus n. sp., Y. brevis n. sp., Y. katherinae n. sp., Y. longus n. sp., Y. pusillus n. sp., Y. velatus n. sp., and Y. virgulifer n. sp. are described, the New Guinean species Y. micans (Klausnitzer, 1973) (= Cyphon paramicans Klausnitzer, 1973, n. syn.), Y. mutilatus n. sp., Y. ruficollis n. sp., and Y. rugosus n. sp. are  described or redescribed from types, respectively. Three Australian species known only in the female sex are described under informal designations.